Predictors of Fear of Intimacy among University Students - Elifnur Barış; Özkan Çıkrıkçı; Neslihan Çıkrıkçı (Uluslararası Türk Eğitim Bilimleri Dergisi)
The study, which aims to examine the association between fear of intimacy, irrational thoughts and alexithymia in university students, was carried out in a correlational design based on a quantitative research approach. To collect the data, Fear-of-Intimacy Scale (FIS), Toronto Alexithymia Scale (TAS-20) and Irrational Beliefs Test (IBT) were used. The data were analysed with SPSS software. Pearson Product Moments Correlation Coefficient was used to examine the associations among fear of intimacy, irrational thoughts and alexithymia. The result of correlation analysis showed that there is a statistically significant association between fear of intimacy and alexithymia. Hierarchical regression analysis was applied to determine the original contribution of irrational thoughts and alexithymia in the explanation of fear of intimacy. In the first step, the predictive strength of irrational thoughts, need for approval, high expectations, tendency to blame and fear of intimacy were examined. The first regression model was significant and accounted for 6.8% of the total variance of fear of intimacy. It was determined that the tendency to blame and helplessness contributed significantly to the model. In the second step, alexithymia was added to the model with sub-dimensions. The second regression model was significant and accounted for 23.5% of the total variance of fear of intimacy. When the R2 change values were examined, the original contribution of the sub-dimensions of alexithymia to the total variance of fear of intimacy was 16.7%.